Comparison of potential biomarker, ACTN3 rs1815739 polymorphism, for athletic performance of Turkish athletes: ACTN3 Polymorphism in Turkish Athletes - Dogan, Murat; Tacal Aslan, Beste; Ulucan, Korkut (Cellular and Molecular Biology, 2022)
α-Actinin-3 is one of the key components of the Z-line structure of sarcomeres and also have importance in muscle cell signaling processes. Therefore, α-Actinin-3 gene rs1815739 polymorphism is one of the most analysed potential genetic biomarkers in sports genetic studies. We aimed to evaluate the genotypic and allelic distribution of α-Actinin-3 gene rs1815739 polymorphism in Turkish athletes. For this purpose, a total of 131 athletes (39 cyclists, 34 sprinters and distance athletes, 33 volleyball players, 15 bodybuilders and 10 ironmen) and 89 sedentary individuals were enrolled in the study. Genomic DNA from venous blood were isolated by using the PureLink DNA isolation kit by following the manufacturers’ instructions. The α-Actinin-3 rs1815739 genotyping was carried out by Real-time PCR using the commercially provided Taqman Genotyping Assay. The statistical evaluations were assessed by the chi-square testing using the GraphPad InStat statistical package. Results showed that cyclists, ironmen and volleyball players showed statistically significant differences in terms of the genotype when compared to the controls. The OR of having the dominant trait (RR genotype vs. RX+XX combined) was 0.5 (95%CI: 0.28–0.91; P= 0.02) which was statistically significant, while the OR of having the recessive trait (XX genotype vs. RR+RX combined) was 3.76 (95%CI: 1.82-7.39; P=0.0002). Our findings indicated that the α-Actinin-3 gene rs1815739 RR genotype was more prevalent in the sprinters and distance athletes. In the bodybuilders, cyclists, and ironmen it was found that they were harboring the RR and RX genotype equally. According to the results, we suggest the α-Actinin-3 rs1815739 as a potential biomarker for personal training programs.